18F-AzaFol for Detection of Folate Receptor-β Positive Macrophages in Experimental Interstitial Lung Disease—A Proof-of-Concept Study - Schniering, Janine; Benešová, Martina; Brunner, Matthias; Haller, Stephanie; Cohrs, Susan; Frauenfelder, Thomas; Vrugt, Bart; Feghali-Bostwick, Carol; Schibli, Roger; Distler, Oliver; Müller, Cristina; Maurer, Britta (Frontiers in Immunology, 2019)
Background Interstitial lung disease (ILD) is a common and severe complication in rheumatic diseases. Folate receptor-β is expressed on activated, but not resting macrophages which play a key role in dysregulated tissue repair including ILD. We therefore aimed to pre-clinically evaluate the potential of 18F-AzaFol-based PET/CT (positron emission computed tomography/computed tomography) for the specific detection of macrophage-driven pathophysiologic processes in experimental ILD. Methods The pulmonary expression of folate receptor-β was analysed in patients with different subtypes of ILD as well as in bleomycin (BLM)-treated mice and respective controls using immunohistochemistry. PET/CT was performed at days 3, 7, and 14 after BLM instillation using the 18F-based folate radiotracer 18F-AzaFol. The specific pulmonary accumulation of the radiotracer was assessed by ex vivo PET/CT scans and quantified by ex vivo biodistribution studies. Results Folate receptor-β expression was 3- to 4-fold increased in patients with fibrotic ILD, including idiopathic pulmonary fibrosis and connective tissue disease-related ILD, and significantly correlated with the degree of lung remodelling. A similar increase in the expression of folate receptor-β was observed in experimental lung fibrosis, where it also correlated with disease extent. In the mouse model of BLM-induced ILD, pulmonary accumulation of 18F-AzaFol reflected macrophage-related disease development with good correlation of folate receptor-β positivity with radiotracer uptake. In the ex vivo imaging and biodistribution studies, the maximum lung accumulation was observed at day 7 with a mean accumulation of 1.01 ± 0.30% injected activity/lung in BLM-treated versus control animals (0.31 ± 0.06% % injected activity/lung; p<0.01). Conclusion Our preclinical proof-of-concept study demonstrated the potential of 18F-AzaFol as a novel imaging tool for the visualisation of macrophage-driven fibrotic lung diseases.